Deciphering the pathways for evaluation of nanotoxicity: Stumbling block in nanotechnology - Shashank Shekhar (Elsevier, 2021)
Nanosafety has been a subject of scrupulous indagation attributed to the ambiguity in terms of harmonizing and perceiving the nano risk evaluation. Nanotoxicity is an emanate pigeonhole of nanotechnology. The burgeoning of commercial products grafted with engineered nanomaterials has been escalated exponentially. Inevitably, the profile of nanomaterials and their repercussions on the ecosystem and mankind must be meticulously assessed. The research fraternity has to evolve innovations to prognosticate the unsought nuisance that does not prevail yet in the frame of reference with nanotoxicity due to the proliferation in the utilization of nanomaterials for consumers' product. Besides, it is imperative to contemplate whether the size is the only characteristic that matters for the detrimental impacts of nanoscale materials. The design and development of safe nanomaterials substantially in drug discovery could be a benchmark. As safety assessment is of utmost importance, therefore it is pre-eminent to lessen animal analysis by the inception of auxiliary or prognostic in silico and in vitro methods which has become a precedence. To perceive the paradigms in nanotoxicity, this robust indagation will provide comprehensive exploration in clearance, kinetics, metabolism, mapping of fate, and physical properties of toxicity of nanomaterials. First, the different characteristics of engineered nanomaterials linked to different toxicological effects is presented. Accordingly, the mechanism by which nanoparticles exhibit toxicity is delineated to aid in nanoparticle redesign to reduce their impact. Second, an overview of the physiochemical techniques and biochemical methodologies adopted for characterization of nanoparticles for testing and screening their toxicological effects is presented. Third, adverse impact of nanoparticle toxicity on human and environment is highlighted. Finally, the challenging pathways and significant strategies to eradicate the risk of nanotoxocity is addressed to proffer a solid rationale in translating the promises of nanotechnology.